Griselda Fights Back: Converting the Prodigal Husband in The London Prodigal - Korell, Hannah (Early Theatre, 2025)
Scholars often contextualize the faithful wife archetype as an iteration of the exhaustingly obedient ‘Patient Griselda’ trope. However, this essay demonstrates the significance of these characters to conversion narratives, showing the agency and power wives were granted to return their wayward husbands to family values, economic and sexual restraint, and the spread of Christianity through reproduction. The London Prodigal responds to topical discourses regarding women’s moral responsibility toward men, staging scenarios in which a wife tames her husband without threatening patriarchal structures and is celebrated for it. The play thus offers an important contribution for studying gendered patterns of conversion.